Whispers from The Forest, Local wisdom in forest conservation and utilization - Witasari, Nina (Paramita: Historical Studies Journal, 2022)
Forest utilization and conservation have become a serious problem faced by many countries in the world. Forests in Java have been exploited massively since colonial rule. Exploitation not only by the colonial government but also by the indigenous rulers. Of course, this exploitation has a big impact on the ecology of Java's forests, which then experience a decline in quality and the loss of several forest areas. Behind all the chaos that occurs in forest management in Java, people instinctively have a mechanism to manage and preserve the forest where they live and make a living. The mechanism in question is to use traditions and myths that have grown and developed in society. This research is social history research, which explores the historical sources of Javanese forestry and relates to social changes that occur in society. The method used is the historical research method and is equipped with information obtained from interviews with some informants. From the results of the research conducted, it can be seen that the Javanese people, especially those who still live around the forest, are currently carrying out traditions related to forest maintenance. Although the forest area is shrinking, the tradition is still carried out, for reasons of cultural and economic preservation.Pemanfaatan dan konservasi hutan telah menjadi masalah serius yang dihadapi oleh banyak negara di dunia. Hutan di Jawa telah dieksploitasi secara besar-besaran sejak pemerintahan kolonial. Eksploitasi tidak hanya dilakukan oleh pemerintah kolonial tetapi juga oleh penguasa pribumi. Tentu saja eksploitasi ini berdampak besar terhadap ekologi hutan Jawa yang kemudian mengalami penurunan kualitas dan hilangnya beberapa kawasan hutan. Di balik semua kekacauan yang terjadi dalam pengelolaan hutan di Jawa, masyarakat secara naluriah memiliki mekanisme untuk mengelola dan melestarikan hutan tempat mereka hidup dan mencari nafkah. Mekanisme yang dimaksud adalah dengan menggunakan tradisi dan mitos yang telah tumbuh dan berkembang di masyarakat. Penelitian ini merupakan penelitian sejarah sosial, yang menggali sumber-sumber sejarah kehutanan Jawa dan berkaitan dengan perubahan sosial yang terjadi di masyarakat. Metode yang digunakan adalah metode penelitian sejarah dan dilengkapi dengan informasi yang diperoleh dari wawancara dengan beberapa informan. Dari hasil penelitian yang dilakukan dapat diketahui bahwa masyarakat Jawa khususnya yang masih tinggal di sekitar hutan saat ini menjalankan tradisi yang berkaitan dengan pemeliharaan hutan. Meski luas hutan semakin menyusut, tradisi tersebut tetap dilakukan, dengan alasan pelestarian budaya dan ekonomi.Cite this article: Witasari, N. (2022). Whispers from the Forest: Local Wisdom in forest Conservation and Utilization. Paramita: Historical Studies Journal, 32(1), 23-32. http://dx.doi.org/10.15294/paramita.v32i1.27173